SIMULASI PENGARUH UKURAN PARTIKEL DAN EQUIVALENCE RATIO DALAM PROSES GASIFIKASI TANDAN KOSONG KELAPA SAWIT - Sabar Pangihutan Simanungkalit; Dieni Mansur; Nino Rinaldi (Research Center for Chemistry - LIPI, 2015)
In this study, a simulation for gasification process of oil palm empty fruit bunches waste (OPEFB) using a fixed bed gasifier (throat downdraft) by varying the particle size of OPEFB and equivalence ratio (ER) was investigated. The rate of fuel consumption was 10 kg/h with air as the oxidizing medium and 1 hour process time for 1 batch. Simulation was performed with two-dimensional approach (2D) using Computational Fluid Dynamics (CFD) ANSYS FLUENT 14 software. Simulation results show that ideal amount of equivalence ratio (ER) for gasification process of OPEFB pellets with diameter (Ï†) of 6 mm and 8 mm is 0.1 â‰¤ ER â‰¤ 0.2. ER variation affects the higher heating value of syngas (HHV), the carbon efficiency (Î·C), gasification efficiency and temperature distribution in the gasification reactor. Variations in particle size did not have a significant effect in the gasification process.Keywords: CFD, OPEFB gasification, particle size, equivalence ratio